Proceedings of 38th International Cosmic Ray Conference — PoS(ICRC2023) 2023
DOI: 10.22323/1.444.0953
|View full text |Cite
|
Sign up to set email alerts
|

The Scientific Performance of the The Moon Burst Energetics All-sky Monitor (MoonBEAM)

Abstract: MoonBEAM is a SmallSat concept placed in cislunar orbit developed to study the progenitors and multimessenger/multiwavelength signals of transient relativistic jets and outflows and determine the conditions that lead to the launching of a transient relativistic jet. The advantage of Moon-BEAM is the instantaneous all-sky coverage due to its orbit, which maximizes the gamma-ray transient observations and provides upperlimits for non-detections. Earth blockage and detector downtime from the high particle activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…This energy range (also sub-MeV) is where phenomena like the Cosmic X-ray Background (CXB) or Gamma Ray Bursts (GRBs) are monitored. There were presentation of balloons like CXBe, the flexible X-ray detector focused on the CXB studies [1], POLAR-2, the next generation of GRB polarization detector that will be located in the Chinese Space Station (CSS) after the successful results of POLAR [2], the MoonBEAM cislunar SmallSat design [3] or XL-Calibur, a proposal for a balloon-borne X-ray polarimeter [4].…”
Section: The Kev Energy Rangementioning
confidence: 99%
“…This energy range (also sub-MeV) is where phenomena like the Cosmic X-ray Background (CXB) or Gamma Ray Bursts (GRBs) are monitored. There were presentation of balloons like CXBe, the flexible X-ray detector focused on the CXB studies [1], POLAR-2, the next generation of GRB polarization detector that will be located in the Chinese Space Station (CSS) after the successful results of POLAR [2], the MoonBEAM cislunar SmallSat design [3] or XL-Calibur, a proposal for a balloon-borne X-ray polarimeter [4].…”
Section: The Kev Energy Rangementioning
confidence: 99%
“…The Moon Burst Energetics All-sky Monitor (MoonBEAM) is a proposed gamma-ray instrument intended for cis-lunar orbit with highly sensitive detectors to observe relativistic astrophysical explosions in near-real time over the entire sky instantaneously for 2.5 years [22]. The mission objective to evaluate relativistic transients produced from the mergers of compact objects,…”
Section: The Moon Burst Energetics All-sky Monitor (Moonbeam)mentioning
confidence: 99%
“…Preliminary work based on GBM GRBs with IPN localizations has found that MoonBEAM will need to localize to ∼10 deg 2 in order to classify an MGF at the 90% confidence level and 100 deg 2 to classify sufficiently bright MGFs at the 75% confidence level. As an instrument of the IPN, the median width of timing annuli for triggered events should be of the order of several degrees [22]. In instances where the IPN cannot localize an MGF to a host galaxy, temporal and spectral analysis as discussed in Section 3, will be used.…”
Section: Pos(icrc2023)1515mentioning
confidence: 99%